Injerencia y autonomía - Lucrecia Molinari (Revista de Estudios sobre Genocidio, 2026)
This article describes the establishment of a counterinsurgency infrastructure in El Salvador in the early 1960s by the United States, in contrast to the repressive strategy implemented during the administration of the Salvadoran president General Julio A. Rivera (1962-1967), coinciding with a favorable economic period and a certain political opening.To this end, a series of declassified documents from U.S. agencies were analysed. Their level of thoroughness and detail shed light on some of the conclusions drawn from the specialized literature.